A Pengaruh Model Pembelajaran Problem Based Learning Berbantuan Media Ular Tangga Terhadap Hasil Belajar Siswa Kelas V - Ananda, Shavira Diah; Khamdun, Khamdun; Masfuah, Siti (P2M STKIP Siliwangi, 2024)
This research aims to determine the difference in average student learning outcomes before and after using the problem based learning model in science and science learning and improving student learning outcomes by using the problem based learning model assisted by snakes and ladders media in class V of SDN 4 Bantrung in the 2023 academic year/ 2024. The reason for choosing class V was because researchers found that the learning outcomes of class V students were below the KKTP. Data collection techniques in this research used the normality test, paired sample t test, N-gain test. The research results before learning the average score obtained was 45.1 and after learning students got an average score of 76.3. The results of the paired sample t test showed a significance value of 0.001, so it can be concluded that there is a significant difference. In the n-gain test, the value obtained was 0.57 or 0.57 > 0.7, so the n-gain criterion obtained was high.